The cellophane bees of Colletes Latreille (Hymenoptera: Colletidae) from Xizang (Tibet), China - Ferrari, Rafael R.; Niu, Ze-Qing; Kuhlmann, Michael; Zhang, Dan; Zhu, Chao-Dong (Zootaxa, 2021)
We present information about the known species of the genus Colletes Latreille found in Xizang (China), including an integrative approach to taxonomy for many of the species. A new species belonging to the C. clypearis Morawitz group, C. splendidus Ferrari, Niu & Zhu sp. nov., is described. Colletes sichuanensis Kuhlmann and C. tuberculatus Morawitz are recorded from Xizang for the first time. The suspected occurrences of both C. bischoffi Noskiewicz and C. packeri Kuhlmann in China are confirmed and their presence in Xizang are also established for the first time. We show that C. fulvicornis Noskiewicz was wrongly recorded from Xizang previously and, therefore, the species is herein removed from the list of the Tibetan Colletes. Thus, 26 species of the genus are now known from Xizang. The putative occurrence of C. annejohnae Kuhlmann in Xizang could not be confirmed, but the species is nonetheless included in the scope of this paper to facilitate its identification by future studies. An illustrated key for the Tibetan species of Colletes is provided.